Emotional intelligence and teaching tutoring in pre-professional internships at a limeña state university - Florian Angulo, Nilda (2020)
Abstract The research we present is born from the interest of improving the capacities related to pre-professional practices, the same ones that prepare us to function as teaching professionals at the end of university studies, we have observed from our university experience students who showed insecurity and emptiness during Acting in the aforementioned courses related to the aforementioned practices, the study is carried out in students of the last year of education in a public university in Lima. The sample was 40% of the total percentage of students (122 future professionals from the X semester of the pre-professional practice course). The present research aims to get to know and identify in a real and objective way the relationship between teacher tutoring with the emotional intellect in pre-professional practitioners who are about to graduate. Due to the characteristics and function of this study, it is quantitative, descriptive, correlational, cross-sectional. We used the REUVEN BAR-ON Test, for data collection for variable X, related to the E.I, as well as a LIKERT questionnaire for variable Y related to teacher tutoring. According to the statistical data of the proposed study, we confirm the general hypothesis, determining a significant relationship between the teaching accompaniment and emotional intelligence in the pre-professional practice students in question. It is concluded that there are some divergences and shortcomings in terms of the emotional aspect and the professional - pedagogical skills, in the last cycle practitioners; since they do not express forceful answers.